Sosialisasi Hukum Konstitusi Tentang Karakter Mulia - Arlis (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
The main issues of this study are about socializing constitutional law on noble character. The research is aimed at determining students' understanding of constitutional law on noble character. The method used is empirical legal research with an approach to the integration of science and legal intensity. The results showed that after socialization, students understood the constitutional law on noble character. The understanding in question includes noble character in the context of Divine Constitutional Law, Prophetic Constitutional Law, Indonesian Constitutional Law, and Andalasian Character. The classification of noble character is very diverse whose essence is the Qur'an character. The character figure of the Qur'an is the Prophet Muhammad SAW inherited by the ulama. The character of the Qur'an became the best and highest standard of character to improve the morale of the nation. Students understand that the mainstay character is a noble character that is coherent with the character of the Qur'an. Students' understanding is important to be followed up with the application of constitutional law with all laws and regulations and implementing regulations All regulations on character are formulated, determined, and applied imbued with a noble character, namely the Qur’an character.